INTEGRATING MANAGEMENT CONTROL SYSTEMS AND ASWAJA CULTURE IN NAHDLATUL ULAMA HIGHER EDUCATION GOVERNANCE - Firdausyi Ayudya Wardani; Dwi Suhartini (ZILLZELL MEDIA PRIMA, 2026)
This study examines the integration of the Management Accounting Control System (MACS) using the Levers of Control (LoC) framework with Aswaja cultural values in realizing good university governance at Nahdlatul Ulama University Sidoarjo. Employing a qualitative case study approach, data were collected through in-depth interviews with four levels of management and supported by institutional document analysis. The findings reveal that the implementation of the control system at UNUSIDA is not driven mechanistically by bureaucratic mechanisms but is dynamically governed by theological and cultural forces. Belief systems rooted in Aswaja values, particularly tawasuth (moderation), tasamuh (tolerance), and the